2013
DOI: 10.1021/jp403753z
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-glutamic acid)-Decorated Hybrid Colloidal Particles from Complex Particle-Templated Silica Mineralization

Abstract: We report the synthesis of polyelectrolyte complex (PEC) particles by mixing the negatively and positively charged polyelectrolytes, poly(L-glutamic acid) (PGA) and poly(2-(N,N-diethylamino) ethylmethacrylate) (PDEAEMA), and the use of negatively charged PEC particles as colloidal templates for silica mineralization under ambient conditions. The structure and property of PEC particles, as well as polypeptide chain conformation, were found to depend on the mixing weight percentage, polymer molecular weight, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
3
9
0
Order By: Relevance
“…As shown in Figure 2b, the two main peaks near −100 ppm and −110.5 ppm are attributed to Q 3 [Si(OSi) 3 (OH)] and Q 4 [Si(OSi) 4 ] with relative percentages of 30.2% and 69.8% respectively, which suggests the formation of well-condensed silica under the catalysis of NH 2 -Alginate. These results are in good agreement with the previous report that the mineralized silica using amine-containing polymers as catalysis and template exhibited a Q 4 /Q 3 ratio from 1.0 to 2.5 [25,26,27,28,29]. …”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 2b, the two main peaks near −100 ppm and −110.5 ppm are attributed to Q 3 [Si(OSi) 3 (OH)] and Q 4 [Si(OSi) 4 ] with relative percentages of 30.2% and 69.8% respectively, which suggests the formation of well-condensed silica under the catalysis of NH 2 -Alginate. These results are in good agreement with the previous report that the mineralized silica using amine-containing polymers as catalysis and template exhibited a Q 4 /Q 3 ratio from 1.0 to 2.5 [25,26,27,28,29]. …”
Section: Resultssupporting
confidence: 93%
“…DLS analysis revealed that discrete polypeptide/silica hybrid nanogels can be prepared, evidenced by little change in sizes before and after silica deposition ( Table 2). FTIR analysis confirmed the deposition of silica in the polypeptide nanogels, as evidenced by the presence of silica absorption bands (data not shown) [50,51]. TEM analysis showed that their sizes were comparable with those determinded by DLS analysis (Fig.…”
Section: Preparation and Characterization Of Pll-g-lipo/silica Hybridsupporting
confidence: 59%
“…FTIR analysis confirmed the deposition of silica in the polypeptide hydrogels, as evidenced by the silica absorption bands at 469 (SieOeSi bend), 801 (SieOeSi symmetric stretch), 960 (SieOeH stretch), 1092 and 1207 cmÀ1 (SieOeSi antisymmetric stretch) (Fig. 5a) [50,51]. From SEM, FTIR, and EDX analyses, the results indicated that silicas were occluded in the gel network.…”
Section: Preparation and Characterization Of Pll-g-lipo/silica Hybridmentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, their properties can be further tuned via formation conditions [2][3][4] or post-treatment modification. [5][6][7][8][9][10] As many important biological macromolecules, such as DNA, RNA, polypeptides or polysaccharides are highly charged PEs, PECs are also promising materials in the fields of biotechnology and medicine. 11 The role of water in hydrated PECs is of great importance for their thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%